Pengaruh Motivasi Kerja dan Kompensasi Pada Kinerja Karyawan PT BCA Finance (Cabang Bekasi) - Prasetio, Resky; Satriansyah, Arief (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
This study aims to analyze the effect of motivation and compensation on employee performance at PT BCA Finance. The research method used is a quantitative approach with data collection through questionnaires distributed to employees as respondents. The data obtained were then analyzed using multiple linear regression to determine the simultaneous and partial effects of the motivation and compensation variables on employee performance. The statistical method used is called the traditional method because it has been used for a long time and has become established as a method for research. This method is referred to as the positivistic method because it is based on the philosophy of positivism. The research results indicate that motivation and compensation together have a positive and significant influence on employee performance. Partially, both motivation and compensation also have a positive influence on improving employee performance. These findings indicate that efforts to enhance motivation and provide fair compensation can be effective strategies for improving employee performance at PT BCA Finance. Therefore, the company is advised to continue paying attention to both aspects in order to achieve organizational goals optimally. The results of the T-test yielded a significance value of 0.043, and the results of the F-test yielded a value of 2.802.